Способ прогнозирования течения ишемической болезни сердца - Канская Н. В. Наталья Викторовна; Пичугин В. Ф. Владимир Федорович; Чернов А. С. Александр Степанович; Федорова Н. А. Нина Александровна; Канский А. В. Александр Викторович; Решетников В. И. Вадим Игоревич; Позднякова И. А. Ирина Анатольевна; Спирина Л. В. Людмила Викторовна
опубл. 20.10.10, Бюл. № 29